REACTION OF THE CAPACITIVE LINK OF THE HEMOMICROCIRCULATORY BED OF THE ILEUM UNDER OXIDATIVE STRESS CAUSED BY THE INTRODUCTION OF A COMPLEX OF CHEMICAL FOOD ADDITIVES - Bilash, S.M.; Oliinichenko, Ya.O.; Pronina, O.M.; Koptev, M.M.; Pirog-Zakaznikova, A.V.; Donchenko, S.V.; Oliinichenko, M.O. (World of Medicine and Biology, 2025)
Food chemical additives are common exogenous factors that can cause changes in the morphology and biochemical parameters of various organs, including the ileum. Therefore, the purpose of our study was to determine changes in the capacitive link of the hemomicrocirculatory bed of the rat ileum and fluctuations in malondialdehyde levels after complex administration of monosodium glutamate, sodium nitrite, and Ponceau 4R. Histological and morphometric examination of the venules of the mucosa and submucosa, as well as determination of the concentration of malondialdehyde in the ileum homogenate of rats of the control group (receiving saline) and experimental groups (administered the test mixture for 1, 4, 8, 12, 16, 20 weeks) were performed. When assessing changes in morphometric parameters, the reaction of the capacitive link of the hemomicrocirculatory bed was revealed, in particular, vasoconstriction of venules from 1 to 8 weeks, partial recovery to control values at 12 weeks and significant vasodilation after 16 weeks, which persisted until the end of the experiment. Regarding biochemical changes, it was found that introducing a complex of chemical food additives leads to signs of oxidative stress, which was confirmed by an increase in the concentration of malondialdehyde. Thus, it was determined that oxidative stress is one of the pathogenetic mechanisms of morphometric changes in the vessels of the capacitive link.